Micro-nano blocking agent, preparation method thereof and prepared blocking drilling fluid

By preparing micro-nano sealant, using the combination of porous zeolite and modified fiber materials, the problem of poor dispersion of sealant in drilling fluid is solved, tight accumulation and effective sealing in formation cracks are achieved, and the drilling fluid is improved sealing performance.

CN119307238AActive Publication Date: 2025-01-14PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310861970.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14
Estimated Expiration
2043-07-13

AI Technical Summary

Technical Problem

The sealing agent in the existing drilling fluid has poor dispersion in the water-based drilling fluid and cannot effectively enter formation cracks and cracks, resulting in poor sealing effect.

Method used

Using the preparation method of micro-nano sealing agent, porous zeolite is prepared by gelation reaction of ethyl orthosilicate, tetrapropyl ammonium hydroxide and aluminum isopropoxide, and the fiber material is modified with a silane coupling agent and loaded Onto the porous zeolite, a micro-nano sealant with good dispersion in the water-based drilling fluid is formed.

Benefits of technology

Micro-nano sealant is not easy to accumulate in water-based drilling fluid and can be closely accumulated in formation cracks, significantly improving the sealing effect, effectively preventing drilling fluid from entering the formation and reducing the risk of well wall collapse.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a micro-nano blocking agent, a preparation method thereof and a prepared blocking drilling fluid, the preparation method comprises the following steps: S1, tetraethoxysilane, tetrapropylammonium hydroxide and aluminum isopropoxide are subjected to gelation reaction in water to obtain transparent gel; the transparent gel is dried, crushed, heated and roasted, and porous zeolite is obtained; s2, modifying the poly (p-phenylene terephthamide) to obtain a modified fiber material; s3, the modified fiber material is dissolved in a mixed solution of dimethylacetamide and lithium chloride, then the porous zeolite is immersed, the mass ratio of the modified fiber material to the porous zeolite is (4-6): (16-18), after soaking is completed, the modified fiber material is taken out and dried, and the micro-nano blocking agent is obtained. The micro-nano plugging agent prepared by the invention can be more tightly accumulated in cracks, and has a good plugging effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drilling fluids, and in particular to a micro-nano plugging agent and a preparation method thereof, and the prepared plugging drilling fluid. Background Art

[0002] With the rapid increase in demand for oil and gas resources and the advancement of drilling technology, researchers have increased their investment in the exploration and development of deep formation oil and gas resources. Some oil and gas resources are mainly buried in deep layers, and the underground conditions are extremely complex. Therefore, deep and ultra-deep well oil and gas drilling and supporting development technologies have become key factors restricting the development of oil and gas resources. As an important part of drilling engineering, the performance of drilling fluid is directly related to the drilling quality, drilling cost and drilling cycle of deep and ultra-deep wells. With the increase in the depth of the formation, there are more and more complex situations underground, especially the cracks and fissures in the formation, which will cause the drilling fluid to enter the formation through the cracks and fissures after being injected into the wellbore, thereby reducing the strength of the well wall rock, and then causing problems such as well wall collapse.

[0003] For cracks and fissures in the formation, a common treatment method is to add plugging agents to the drilling fluid. The plugging agents are usually in the form of small particles or fibers. The plugging principle is to enter the cracks and fissures and accumulate tightly, thereby isolating the inside of the wellbore from the formation and preventing the drilling fluid from entering the formation. However, most of the conventional plugging agents currently have poor plugging effects. The reason is that the plugging agent particles have poor dispersibility in water-based drilling fluids, and small particles are easy to aggregate into clumps in the drilling fluid, that is, their size becomes larger. As a result, they cannot effectively enter the cracks and fissures for sealing.

[0004] How to improve the plugging performance of plugging agents, that is, how to make the plugging agents disperse well in water-based drilling fluids and accumulate tightly in cracks and fissures, is an urgent problem in the field. Summary of the invention

[0005] In order to solve the problem that the plugging agent has low accumulation density and poor plugging effect in formation fissures, the purpose of the present invention is to provide a micro-nano plugging agent and a preparation method thereof and a plugging drilling fluid prepared therefrom, wherein the micro-nano plugging agent can accumulate more densely in the fissures and has a good plugging effect.

[0006] In order to achieve the above object, the present invention provides a method for preparing a micro-nano plugging agent, which comprises the following steps:

[0007] S1: allowing tetraethyl orthosilicate, tetrapropylammonium hydroxide and aluminum isopropoxide to undergo a gelation reaction in water to obtain a transparent gel; drying and crushing the transparent gel, and then heating and calcining the gel to obtain a porous zeolite;

[0008] S2: modifying poly(p-phenylene terephthalamide) to obtain a modified fiber material;

[0009] S3: dissolving the modified fiber material in a mixture of dimethylacetamide and lithium chloride, and then immersing the porous zeolite, wherein the mass ratio of the modified fiber material to the porous zeolite is 4-6:16-18. After immersion, taking out and drying, the micro-nano plugging agent is obtained.

[0010] In step S1 of the preparation method of the present invention, ethyl orthosilicate, aluminum isopropoxide and tetrapropylammonium hydroxide are used as raw materials to prepare a porous zeolite with a particle size of 200-500nm, which is 1-2 microns smaller than the size of conventional formation fissures, i.e., it can smoothly enter the fissures for plugging.

[0011] In step S2 of the preparation method of the present invention, poly(p-phenylene terephthalamide) is hydrophilically modified using silane coupling agent KH-792, thereby improving its dispersion performance in water. Specifically, silane coupling agent KH-792 is a diamino-type functional group silane. When it is hydrolyzed in water, the -Si(OCH3)3 group is hydrolyzed into a strongly hydrophilic -Si(OH)3. At the same time, the -(CH2)3NH(CH2)2NH2 at the other end of the molecular chain can react with the -COOH group on the surface of poly(p-phenylene terephthalamide) through -NH2 and -NH groups, thereby successfully grafting the coupling agent to the surface of poly(p-phenylene terephthalamide), thereby improving its hydrophilicity and dispersibility. After such modification, since poly(p-phenylene terephthalamide), i.e., the fiber material, has good dispersibility, the micro-nano plugging agent particles are not prone to aggregation in the water-based drilling fluid.

[0012] Step S3 of the preparation method of the present invention is to load the fiber material onto the porous zeolite using a mixed solution of dimethylacetamide and lithium chloride. The specific principle is: in the mixed solution, dimethylacetamide and lithium chloride form (DMAcLi) + Large cation, Li + With Cl - The charge distribution between Cl - With more negative charge, Cl - The ability to attack the H protons in the amide bonds on the poly(p-phenylene terephthalamide) molecular chain is greatly enhanced, and hydrogen bonds are formed with it, thereby destroying the poly(p-phenylene terephthalamide) crystal region grid, and ultimately causing the poly(p-phenylene terephthalamide) macromolecular chain to dissociate and dissolve, and after dissolution, it appears as a clear and transparent solution. When the porous zeolite is placed in it, the dissolved poly(p-phenylene terephthalamide) enters the pores of the porous zeolite and adheres to the surface of the porous zeolite. It is then heat-dried, and under heat treatment, the dimethylacetamide solution gradually evaporates, resulting in (DMAcLi) +The hydrogen bond between the large cation and the poly(p-phenylene terephthalamide) molecular chain is destroyed, so that the poly(p-phenylene terephthalamide) crystal area is regenerated, that is, the dissolved fiber begins to regenerate, and the roots of the regenerated fiber material are fixed in the pores, and the free ends are distributed on the outside of the porous zeolite.

[0013] According to a specific embodiment of the present invention, preferably, in S1, the mass ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and aluminum isopropoxide is 12-14:2-4:5-7.

[0014] According to a specific embodiment of the present invention, preferably, in S1, the gelation reaction temperature is 35-45° C., and the reaction time is 15-25 min.

[0015] According to a specific embodiment of the present invention, preferably, in S1, the heating temperature is 160-180°C and the heating time is 8-9h.

[0016] According to a specific embodiment of the present invention, preferably, in S1, the calcination temperature is 560-600° C., and the heating time is 4-5 h.

[0017] According to a specific embodiment of the present invention, preferably, the particle size of the porous zeolite is 200-500 nm. The particle size of the porous zeolite is controlled during the crushing process of S1.

[0018] According to a specific embodiment of the present invention, preferably, in S2, the modification method of poly(p-phenylene terephthalamide) comprises: subjecting poly(p-phenylene terephthalamide) to ultrasonic treatment in acetone and in a silane coupling agent solution in sequence to obtain the modified fiber material.

[0019] According to a specific embodiment of the present invention, preferably, the modification method further comprises: washing and drying the poly(p-phenylene terephthalamide) after ultrasonic treatment.

[0020] According to a specific embodiment of the present invention, preferably, the silane coupling agent solution includes at least one of KH-792 silane coupling agent, KH-902 silane coupling agent, and KH-571 silane coupling agent, preferably KH-792 silane coupling agent with a mass concentration of 25-28wt%.

[0021] According to a specific embodiment of the present invention, preferably, the ultrasonic power of the ultrasonic treatment is 70-90W, and the treatment time is 3-4h.

[0022] According to a specific embodiment of the present invention, preferably, in S3, the mass ratio of the porous zeolite, the modified fiber material and the mixed solution of dimethylacetamide and lithium chloride is 4-6:16-18:34-36.

[0023] According to a specific embodiment of the present invention, preferably, in S3, the mass ratio of dimethylacetamide to lithium chloride in the mixed solution of dimethylacetamide and lithium chloride is 1:9-11.

[0024] According to a specific embodiment of the present invention, preferably, in S3, the immersion time of the porous zeolite is 2-3 hours.

[0025] According to a specific embodiment of the present invention, preferably, in S3, the drying temperature is 60-70° C., and the drying time is 40-60 min.

[0026] According to a specific embodiment of the present invention, preferably, the preparation method of the micro-nano plugging agent comprises the following steps:

[0027] This embodiment is used to prepare a micro-nano plugging agent, and includes the following steps:

[0028] S1. Synthetic porous zeolite:

[0029] S11, adding 20-25 parts by weight of water, 12-14 parts by weight of ethyl orthosilicate and 5-7 parts by weight of aluminum isopropoxide into a three-necked flask and stirring;

[0030] S12, adding 2-4 parts by weight of tetrapropylammonium hydroxide into a three-necked flask, stirring in a water bath, to obtain a transparent gel;

[0031] S13, drying and grinding the transparent gel obtained in step S12, and then transferring it to a hydrothermal kettle and heating it at 160-180° C. for 8-9 hours;

[0032] S14, transferring the material treated in step S13 into a muffle furnace, and calcining at 560-600° C. for 4-5 hours to obtain a porous zeolite with a particle size of 200-500 nm;

[0033] S2. Modifying the dispersion performance of poly(p-phenylene terephthalamide) to obtain a modified fiber material:

[0034] S21, soaking poly(p-phenylene terephthalamide) in acetone, and ultrasonically treating for 3-4 hours at an ultrasonic power of 70-90 W;

[0035] S22, taking out the material treated in step S21 and placing it in a silane coupling agent KH-792 solution with a concentration of 25-28%, and ultrasonically treating it for 3-4 hours at an ultrasonic power of 70-90 W;

[0036] S23, taking out the material treated in step S22, washing it with deionized water and then drying it to obtain a modified fiber material;

[0037] S3, preparing a first mixed solution of dimethylacetamide and lithium chloride, wherein the mass ratio of lithium chloride to dimethylacetamide is 1:9-11;

[0038] S4, placing the modified fiber material obtained in step S2 into the first mixed solution obtained in step S3, stirring at room temperature, and obtaining a second mixed solution after the modified fiber material is completely dissolved;

[0039] S5, soaking the porous zeolite obtained in step S1 in the second mixed solution obtained in step S4 for 2-3 hours;

[0040] S6, transferring the porous zeolite soaked in step S5 to a forced air drying oven for heat drying at a temperature of 60-70°C for a time of 40-60 minutes, and taking it out after heat drying to obtain the micro-nano plugging agent.

[0041] The present invention also provides a micro-nano plugging agent obtained by the preparation method of the micro-nano plugging agent.

[0042] The present invention also provides a plugging drilling fluid, which is prepared from the above-mentioned micro-nano plugging agent.

[0043] In the above-mentioned plugging drilling fluid, preferably, the raw materials of the plugging drilling fluid include, by weight: 3-5 parts of the above-mentioned micro-nano plugging agent, 4-6 parts of bentonite, 0.5-1.5 parts of sodium hydroxide, 2-4 parts of sodium carboxymethyl cellulose, 7-9 parts of xanthan gum, and 60-80 parts of barite.

[0044] The technical solution provided by the present invention has the following beneficial effects:

[0045] The micro-nano plugging agent prepared by the present invention uses porous zeolite with certain dispersibility in water-based drilling fluid as a main body, so that the micro-nano plugging agent is not easy to aggregate in the water-based drilling fluid; in addition, the present invention loads the modified fiber material in the pores of the porous zeolite, so that the root of the modified fiber material is fixed in the pores, and the free end is distributed outside the porous zeolite. When the porous zeolite particles enter the formation fissures, due to the small size of the fissures, that is, the small distance between particles, the free ends of the fiber materials are entangled with each other, so that the porous zeolite particles are more densely stacked in the fissures, and the plugging effect is effectively improved. DETAILED DESCRIPTION

[0046] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0047] Example 1

[0048] This embodiment provides a method for preparing a micro-nano plugging agent, comprising the following steps:

[0049] S1. Synthetic porous zeolite:

[0050] S11, adding 23 parts by weight of water, 13 parts by weight of ethyl orthosilicate and 6 parts by weight of aluminum isopropoxide into a three-necked flask and stirring;

[0051] S12, adding 3 parts by weight of tetrapropylammonium hydroxide into a three-necked flask, stirring in a water bath, to obtain a transparent gel;

[0052] S13, drying and grinding the transparent gel obtained in step S12, and then transferring it to a hydrothermal kettle and heating it at 170° C. for 8.5 hours;

[0053] S14, transferring the material treated in step S13 into a muffle furnace, and calcining at 580° C. for 4.5 h to obtain a porous zeolite with a particle size of 350 nm;

[0054] S2. Modifying the dispersion performance of poly(p-phenylene terephthalamide) to obtain a modified fiber material:

[0055] S21, immersing poly(p-phenylene terephthalamide) in acetone, and ultrasonically treating for 3.5 h at an ultrasonic power of 80 W;

[0056] S22, taking out the material treated in step S21 and placing it in a KH-792 silane coupling agent with a concentration of 26wt%, and ultrasonically treating it for 3.5h at an ultrasonic power of 80W;

[0057] S23, taking out the material treated in step S32, washing it with deionized water and then drying it to obtain a modified fiber material;

[0058] S3, prepare a mixed solution of dimethylacetamide and lithium chloride, where the mass ratio of lithium chloride to dimethylacetamide is 1:10;

[0059] S4, adding the modified fiber material obtained in step S2 to the mixed solution obtained in step S3, stirring at room temperature, and immersing the porous zeolite obtained in step S1 after the modified fiber material is completely dissolved, and the immersion time is 2.5 hours, wherein the mass ratio of the mixed solution, the modified fiber material, and the porous zeolite is 18:17:5;

[0060] S5. The porous zeolite soaked in step S4 is transferred to a forced air drying oven for heat drying at a temperature of 65° C. for 50 min. The zeolite is taken out after heat drying to obtain the micro-nano plugging agent A1.

[0061] Example 2

[0062] This embodiment provides a method for preparing a micro-nano plugging agent, comprising the following steps:

[0063] S1. Synthetic porous zeolite:

[0064] S11, adding 20 parts by weight of water, 12 parts by weight of tetraethyl orthosilicate and 5 parts by weight of aluminum isopropoxide into a three-necked flask and stirring;

[0065] S12, adding 2 parts by weight of tetrapropylammonium hydroxide into a three-necked flask, stirring in a water bath, to obtain a transparent gel;

[0066] S13, drying and grinding the transparent gel obtained in step S12, and then transferring it to a hydrothermal kettle and heating it at 160° C. for 8 hours;

[0067] S14, transferring the material treated in step S13 into a muffle furnace, and calcining at 560° C. for 4 h to obtain a porous zeolite with a particle size of 200 nm;

[0068] S2. Modifying the dispersion performance of poly(p-phenylene terephthalamide) to obtain a modified fiber material:

[0069] S21, immersing poly(p-phenylene terephthalamide) in acetone, and ultrasonically treating it for 3 h at an ultrasonic power of 70 W;

[0070] S22, taking out the material treated in step S21 and placing it in a KH-792 silane coupling agent with a concentration of 25wt%, and ultrasonically treating it for 3h at an ultrasonic power of 70W;

[0071] S23, taking out the material treated in step S32, washing it with deionized water and then drying it to obtain a modified fiber material;

[0072] S3, preparing a first mixed solution of dimethylacetamide and lithium chloride, wherein the mass ratio of lithium chloride to dimethylacetamide is 1:9;

[0073] S4, adding the modified fiber material obtained in step S2 to the mixed solution obtained in step S3, stirring at room temperature, and immersing the porous zeolite obtained in step S1 after the modified fiber material is completely dissolved, and the immersion time is 2 hours, wherein the mass ratio of the mixed solution, the modified fiber material, and the porous zeolite is 9:8:2;

[0074] S5, transferring the porous zeolite soaked in step S4 to a forced air drying oven for heat drying at a temperature of 60°C for 40 minutes, and taking it out after heat drying to obtain the micro-nano plugging agent A2.

[0075] Example 3

[0076] This embodiment provides a method for preparing a micro-nano plugging agent, comprising the following steps:

[0077] S1. Synthetic porous zeolite:

[0078] S11, adding 25 parts by weight of water, 14 parts by weight of tetraethyl orthosilicate and 7 parts by weight of aluminum isopropoxide into a three-necked flask and stirring;

[0079] S12, adding 4 parts by weight of tetrapropylammonium hydroxide into a three-necked flask, stirring in a water bath, to obtain a transparent gel;

[0080] S13, drying and grinding the transparent gel obtained in step S12, and then transferring it to a hydrothermal kettle and heating it at 180° C. for 9 hours;

[0081] S14, transferring the material treated in step S13 into a muffle furnace, and calcining at 600° C. for 5 h to obtain a porous zeolite with a particle size of 500 nm;

[0082] S2. Modifying the dispersion performance of poly(p-phenylene terephthalamide) to obtain a modified fiber material:

[0083] S21, soaking poly(p-phenylene terephthalamide) in acetone, and ultrasonically treating it for 4 hours at an ultrasonic power of 90 W;

[0084] S22, taking out the material treated in step S21 and placing it in a KH-792 silane coupling agent with a concentration of 28wt%, and ultrasonically treating it for 4h at an ultrasonic power of 90W;

[0085] S23, taking out the material treated in step S32, washing it with deionized water and then drying it to obtain a modified fiber material;

[0086] S3, preparing a first mixed solution of dimethylacetamide and lithium chloride, wherein the mass ratio of lithium chloride to dimethylacetamide is 1:11;

[0087] S4, adding the modified fiber material obtained in step S2 to the mixed solution obtained in step S3, stirring at room temperature, and immersing the porous zeolite obtained in step S1 after the modified fiber material is completely dissolved, and the immersion time is 3 hours, wherein the mass ratio of the mixed solution, the modified fiber material, and the porous zeolite is 18:18:5;

[0088] S5, transferring the porous zeolite soaked in step S4 to a forced air drying oven for heat drying at a temperature of 70° C. for 60 min, and taking it out after heat drying to obtain the micro-nano plugging agent A3.

[0089] Example 4

[0090] The present embodiment provides a plugging drilling fluid, and the preparation method thereof is as follows: by weight, 100 parts of water, 5 parts of bentonite, 1 part of sodium hydroxide, 3 parts of sodium carboxymethyl cellulose, 8 parts of xanthan gum, 70 parts of barite, and 4 parts of the micro-nano plugging agent A1 prepared in Example 1 are mixed and stirred to obtain a plugging drilling fluid B1.

[0091] Example 5

[0092] This embodiment provides a plugging drilling fluid, and its preparation method is the same as that of embodiment 4, except that the micro-nano plugging agent A1 is replaced by the micro-nano plugging agent A1 prepared in embodiment 2. A plugging drilling fluid B2 is obtained.

[0093] Example 6

[0094] This embodiment provides a plugging drilling fluid, and its preparation method is the same as that of embodiment 4, except that the micro-nano plugging agent A1 is replaced by the micro-nano plugging agent A3 prepared in embodiment 3. A plugging drilling fluid B3 is obtained.

[0095] Comparative Example 1

[0096] This comparative example provides a drilling fluid, and its preparation method is the same as that of Example 4, except that the micro-nano plugging agent A1 is not added to obtain a drilling fluid D1.

[0097] Comparative Example 2

[0098] This comparative example provides a drilling fluid, the preparation method of which is the same as that of Example 4, except that instead of adding the micro-nano plugging agent A1, a mixture of poly(p-phenylene terephthalamide) and porous zeolite (by mass ratio, poly(p-phenylene terephthalamide) : porous zeolite = 17:5) in an amount equal to that of the micro-nano plugging agent A1 is added to obtain drilling fluid D2.

[0099] Experimental example

[0100] This experimental example is used to test the plugging performance of the plugging drilling fluids B1-B3 prepared in Examples 4-6 and the drilling fluids D1 and D2 prepared in Comparative Examples 1-2. The specific operation is as follows:

[0101] The filtration loss of the newly prepared drilling fluid within half an hour was tested and recorded using a high temperature and high pressure filter loss instrument at room temperature. Filter paper was placed at the bottom of the kettle of the high temperature and high pressure filter loss instrument. Several small holes of 1 micron in size were distributed on the filter paper. The thickness of the filter paper was 5 mm. The results are shown in Table 1.

[0102] Table 1 Drilling fluid loss

[0103] Serial number Filtrate loss / mL Plugging drilling fluid B1 2.1 Plugging Drilling Fluid B2 2.2 Plugging Drilling Fluid B3 2.2 Drilling Fluid D1 54 Drilling Fluid D2 26

[0104] It can be seen from the data in Table 1 that the micro-nano plugging agent prepared by the method provided by the present invention, when added to the drilling fluid system to form plugging drilling fluids B1-B3, has a filtration loss of less than 3 mL within half an hour, which indicates that the micro-nano plugging agent forms a dense accumulation on the surface of the filter paper and inside the pores in a short time, effectively isolating the internal and external environments of the filter loss instrument kettle.

[0105] It can be seen from the drilling fluid D1 as the blank control group that the filtrate in the drilling fluid continued to filter out without adding plugging components, and the filtrate reached 54mL within half an hour. In the drilling fluid D2, since its plugging component is only a mixture of poly(p-phenylene terephthalamide) and porous zeolite, it has a certain plugging effect, but the filtration loss is still large. On the one hand, this is because the fibrous poly(p-phenylene terephthalamide) has not been dispersed and modified, so that the poly(p-phenylene terephthalamide) is entangled with each other in the drilling fluid, increasing the volume of the solid phase particles, and the large volume of solid phase particles cannot enter the pores of the filter paper for effective blocking; on the other hand, the poly(p-phenylene terephthalamide) and porous zeolite that enter the pores of the filter paper cannot be tightly stacked because there is no stable connection between the two, so the blocking of the holes on the filter paper is not thorough enough, so that filtrate is always filtered out through the filter paper. Within half an hour, the continuous filtrate filtered out reached 26mL, and this filtration loss will increase further with time.

[0106] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a micro-nano plugging agent, comprising the following steps: S1: allowing tetraethyl orthosilicate, tetrapropylammonium hydroxide and aluminum isopropoxide to undergo a gelation reaction in water to obtain a transparent gel; drying and crushing the transparent gel, and then heating and calcining the gel to obtain a porous zeolite; S2: modifying poly(p-phenylene terephthalamide) to obtain a modified fiber material; S3: dissolving the modified fiber material in a mixture of dimethylacetamide and lithium chloride, and then immersing the porous zeolite, wherein: The mass ratio of the modified fiber material to the porous zeolite is 4-6:16-18. After soaking, the fiber material is taken out and dried to obtain the micro-nano plugging agent.

2. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S1, the mass ratio of tetraethyl orthosilicate, tetrapropylammonium hydroxide and aluminum isopropoxide is 12-14:2-4:5-7.

3. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S1, the gelation reaction temperature is 35-45°C, and the reaction time is 15-25 minutes.

4. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S1, the heating temperature is 160-180°C and the heating time is 8-9h.

5. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S1, the calcination temperature is 560-600°C, and the heating time is 4-5h.

6. The method for preparing the micro-nano plugging agent according to claim 1, wherein: The particle size of the porous zeolite is 200-500 nm.

7. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S2, the modification method of poly(p-phenylene terephthalamide) comprises: subjecting poly(p-phenylene terephthalamide) to ultrasonic treatment in acetone and in a silane coupling agent solution in sequence to obtain the modified fiber material; Preferably, the modification method further comprises: washing and drying the poly(p-phenylene terephthalamide) after ultrasonic treatment.

8. The method for preparing the micro-nano plugging agent according to claim 7, wherein: The silane coupling agent solution includes at least one of KH-792 silane coupling agent, KH-902 silane coupling agent and KH-571 silane coupling agent, preferably KH-792 silane coupling agent with a mass concentration of 25-28wt%.

9. The method for preparing the micro-nano plugging agent according to claim 7, wherein: The ultrasonic power of the ultrasonic treatment is 70-90W, and the treatment time is 3-4h.

10. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S3, the mass ratio of the porous zeolite, the modified fiber material and the mixed solution of dimethylacetamide and lithium chloride is 4-6:16-18:34-36.

11. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S3, the mass ratio of dimethylacetamide to lithium chloride in the mixed solution of dimethylacetamide and lithium chloride is 1:9-11.

12. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S3, the porous zeolite is immersed for 2-3 hours.

13. The method for preparing the micro-nano plugging agent according to claim 1, wherein: In S3, the drying temperature is 60-70°C and the drying time is 40-60 minutes.

14. A micro-nano plugging agent obtained by the preparation method of the micro-nano plugging agent according to any one of claims 1 to 13.

15. A plugging drilling fluid prepared from the micro-nano plugging agent according to claim 14.

16. The plugging drilling fluid according to claim 15, wherein the raw materials thereof include, by weight: 3-5 parts of the micro-nano plugging agent according to claim 14, 4-6 parts of bentonite, 0.5-1.5 parts of sodium hydroxide, 2-4 parts of sodium carboxymethyl cellulose, 7-9 parts of xanthan gum, and 60-80 parts of barite.

Citation Information

Patent Citations

  • Fibrous water-soluble shielding temporary plugging agent

    CN102268247A

  • Process method for improving temporary plugging rate and plugging removal rate of water-soluble temporary plugging agent

    CN105419754A

  • Oil-based plugging agent and preparation method thereof

    CN109135698A

  • Lost circulation material for drilling fluids

    EP2196516A1

  • Lost circulation material for oilfield use

    US20100298175A1